Iranian`s Cultural Identity: from Theoretical Perspective to Principles - Hasammoddin Ashna; Mohammad Reza Roohani (Taḥqīqāt-i Farhangī-i Īrān)
Identity is one of the most complicated concepts in humanities and social sciences. It is a multi-aspected phenomenon which expresses different meanings from different viewpoints. Generally we can say that Identity is a result of dialect between conceptual system and socio-cultural structures. In this approach, Identity is addressed in relation with ; and so, emphasis on “self” and “others” unit of analysis. But when we focus on “cultural identity”, the relationship between identity and complicated concepts, e.g. culture and nationality, will turn into a mess which then, identity concept can be interpreted by different theoretical approaches. This meaning specially is important in Iran, because Iranian, Islamic and western identity sources affected Iranian people identity in different ages and finally born into contemporary Iranian cultural identity. We can name two different identity approaches here: descriptive approach which describe now and then, and prescriptive or policy approach which regards identity policies. In prescriptive approach, identity elements are general and abstract concepts, because identity change is regarded as an incremental movement .in regard with this basis in identity policy, we can analyze main Iranian cultural identity elements in five domains: religion, language, cultural geography, history and cultural memory, and social system.